Are dry-land strength metrics and forces exerted in-water related with high swimming velocity in young athletes? - Morouço, P. G.; Marinho, D. A.; Marques, M. C. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
This study aimed to assess strength metrics in 3 dry-land exercises, forces exerted inwater in 3 tethering conditions, and to analyze possible relationships between those variables with high swimming velocity. Mean power, mean forces and 50 m maximum swimming velocity, were recorded and calculated for ten male young swimmers. High correlations were noticed between the dry-land exercises, with the lat pull down presenting the higher correlation with swimming velocity (r = 0.695, p = 0.026). The higher correlation of swimming velocity with forces exerted in-water was observed through the only arms condition (r = 0.762, p = 0.010). Results suggest that for high swimming velocity forces exerted in-water by the arms are a major criteria for success, and that lat pull down may be an appropriate dry-land exercise for its development.